Monitoring comparison of anaesthetised healthy sheep submitted to four different intraabdominal pressures - Liana Villela de Gouvea; Paulo Roberto Loureiro do Nascimento; Thiago Ravache Sobreira Leite; André Luís de Souza Teixeira; Paulo César do Amaral Ribeiro da Silva; José Aurelino Damasceno Ferreira Filho; Michel José Sales Abdalla Helayel; Amary Nascimento Júnior; Marina Galindo Chernard; Luiza de Albuquerque Carvalho; Pedro Leme Silva; Daniel Augusto Barroso Lessa (Ciência Animal Brasileira)
The sheep model is used for a variety of laparoscopy studies, as well as in routine procedures such as oocyte aspiration and artificial insemination. However, little information is published about the monitoring parameters and ventilatory mechanics changes and when they begin to occur during these procedures with pneumoperitoneum. Ten adult, healthy, non-pregnant Santa Inês sheep were anesthetized and mechanically ventilated (VT, 15 ml kg−1; positive end-expiratory pressure, 3 cmH2O; FiO2, 1.0), randomized in a crossover design for 4 different intra-abdominal pressures (IAP) as treatments: 0 mmHg (G1), 10 mmHg (G2), 12 mmHg (G3) and 15 mmHg (G4), for 60 min, with data collected every 10 min (HR, SpO2, body temperature, ETCO2, SAP, DAP, MAP, MACinsp, MACexp, Ppeak,RS, VT and Cdyn). End-expiratory CO2 tension (ETCO2) increased over time in all groups, except in G1. Peak airway pressure (Ppeak) and dynamic compliance (Cdyn) increased over time in all groups but were significantly higher in G3 and G4 from 20 min onwards. The minimum alveolar concentration (MAC) during inspiration and expiration increased over time in all groups, except G1. Within 20 minutes of the procedure, it was possible to notice that in the groups with higher IAP (G3 and G4) there was an increase in Ppeak and Cdyn, compatible with other findings of clinical importance such as an increase in ETCO2, a decrease in VT and SpO2. Therefore, 20 minutes after the procedure, monitoring must be more careful, especially in animals with previous health conditions.